Moving passions: theories of affect in Renaissance love discourse and Shakespeare's Elizabethan plays - Gordon Colette (Department of English Language and Literature, 2018)
The 1998 film, Shakespeare in Love, sets Will Shakespeare (and itself) the challenge to "show the nature and truth of love ... to make it [love] true" - with an ideal presentation of Romeo and Juliet. The film finally achieves this by ensuring that Will and Viola end on stage as Romeo and Juliet, playing the parts they respectively inspire. The film, and the play within the film, can achieve the satisfactory embodiment of true love only, it seems, through the replacement of stage lover/player with 'real' lovers. The film attempts to unite love and art, but finds stage representation naturally adverse to its idea of true (authentic) love. Persuasion is similarly suppressed as inimical to the film's notion of art as expressive (of authentic emotion). But, where love is conceived as spectacularly mobile, mimetic and transformative - as I show it was, in the early modem period - to effectively communicate and to affectively produce love are, of necessity, linked. Joseph Roach has pointed persuasively to rhetoric's strong connection with humoral theory. Using texts from Wilson, Wright and Bulwer, I pursue and extend his focus on the early modem passionate, rhetorical actor; the interface between body and mind; and the possibility of powerful rhetorical passions, generated in performance. The film assumes (true) love as an emotion that is rare, elusive and, crucially, authentic. But as a renaissance 'passion', love would have very different qualities. Such passions would be vital, dynamic forces, directly communicable and contagious, commonly available and commonly shared. I argue that love, more properly "affect" or "passion", was frequently valued in the Renaissance, not as a stable locus of inner truth and authenticity (the thinking that necessitates the suppression of the actor in Shakespeare in Love), but for its very ability to 'move' where, in Rosemond Tove's words, "the unity of the process moving: persuading is not disturbed." I look for this movement in a number of Shakespeare's Elizabethan plays, particularly The Two Gentlemen of Verona, Love's Labours Lost, A Midsummer Night's Dream, Romeo and Juliet, As You Like It, and Twelfth Night and examine the forms of passion in compelling topoi that attend love in the plays - Petrarchan tropes powerfully linked to early modem ideas of representation (especially dramatic) and the interaction, in imitation, between bodies and minds. Early modem passions threaten clear distinctions between desires and emotions, body and mind and, importantly, self and other. I argue that, when passions are communicable and shared, the passionating actor participates in ideal forms beyond realistic imitation or personal, interior emotional experience - a process to which the real, ideal love of Shakespeare in Love is superfluous.